2011
DOI: 10.1021/ja2065522
|View full text |Cite
|
Sign up to set email alerts
|

Live-Cell-Permeant Thiophene Fluorophores and Cell-Mediated Formation of Fluorescent Fibrils

Abstract: In our search for thiophene fluorophores that can overcome the limits of currently available organic dyes in live-cell staining, we synthesized biocompatible dithienothiophene-S,S-dioxide derivatives (DTTOs) that were spontaneously taken up by live mouse embryonic fibroblasts and HeLa cells. Upon treatment with DTTOs, the cells secreted nanostructured fluorescent fibrils, while cell viability remained unaltered. Comparison with the behavior of other cell-permeant, newly synthesized thiophene fluorophores show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 38 publications
1
75
1
Order By: Relevance
“…[1][2][3][4][5][6] In addition, the recent development of simple methods for their preparation has enabled the synthesis of unexplored families of sulfur-oxygenated oligoand polythiophenes with potential applications spanning from organic electronics to chemical biology. [7][8][9][10][11][12][13][14][15][16][17][18][19] The incorporation of strong electron acceptor TDO moieties deeply affects the HOMO-LUMO energy levels of the material causing a substantial reduction of the energy gap. [20][21][22][23][24] Moreover, it may induce a change in the charge transport properties from p-to n-type, 7,10,25 as well as in the self-assembly properties due to additional intra-and intermolecular hydrogen nonbonding interactions.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, the recent development of simple methods for their preparation has enabled the synthesis of unexplored families of sulfur-oxygenated oligoand polythiophenes with potential applications spanning from organic electronics to chemical biology. [7][8][9][10][11][12][13][14][15][16][17][18][19] The incorporation of strong electron acceptor TDO moieties deeply affects the HOMO-LUMO energy levels of the material causing a substantial reduction of the energy gap. [20][21][22][23][24] Moreover, it may induce a change in the charge transport properties from p-to n-type, 7,10,25 as well as in the self-assembly properties due to additional intra-and intermolecular hydrogen nonbonding interactions.…”
mentioning
confidence: 99%
“…Theoretical calculations carried out on a system consisting of three sequences of the tripeptide Gly-Pro-HyPro (as a model for procollagen chains) in the presence of 5 support this hypothesis. 25 The calculations predicted an energetically favorable configuration ( Figure 7C) involving a hydrogen bond between the HyPro and one of the oxygen atoms of 5.…”
Section: ■ Microfibers Spontaneously Coassembled With Proteins Insidementioning
confidence: 96%
“…25 When dissolved in physiological solution, they were spontaneously taken up by live mouse embryonic fibroblasts (NIH-3T3) and HeLa cells. 25 DTTO 5 was also successfully tested with bone-marrow-derived human fibroblasts (BMFbs) 36 and mouse neuroblastoma cells (B104). 37 Figure 6A shows laser scanning confocal microscopy (LSCM) images of the spontaneous uptake of 5 by BMFbs as a function of time.…”
Section: ■ Microfibers Spontaneously Coassembled With Proteins Insidementioning
confidence: 99%
See 1 more Smart Citation
“…Giovanna Barbarella group (University of Bologna, Italy) has succeeded in developing oligothiophenes for stem cell imaging [77] and has also shown that selected oligothiophenes have the capability to distinguish protein types inside living cells [78]- [80]. It is most likely that Barbarellas thiophene probes, due to a succinimidyl ester group, covalently binds to amino groups of the intracellular protein target.…”
Section: Lcos As Fluorescent Reportersmentioning
confidence: 99%